2020
DOI: 10.3390/nu12092518
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Vitamin D Supplementation Improves Microcirculation and Reduces Inflammation in Diabetic Neuropathy Patients

Abstract: We assessed the effect of different doses of vitamin D supplementation on microcirculation, signs and symptoms of peripheral neuropathy and inflammatory markers in patients with type 2 diabetes (T2DM). Sixty-seven patients with T2DM and peripheral neuropathy (34 females) were randomized into two treatment groups: Cholecalciferol 5000 IU and 40,000 IU once/week orally for 24 weeks. Severity of neuropathy (NSS, NDS scores, visual analogue scale), cutaneous microcirculation (MC) parameters and inflammatory marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
1
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 40 publications
4
46
1
13
Order By: Relevance
“…Our data showed that Bacteroidetes phylum ( Figure 6 A) specifically Parabacteroides genus ( Figure 6 B) was negatively correlated with CNFL, ( p = 0.03625 and 0.00179 respectively). Vitamins D and B have been previously reported to play a potential role in the pathophysiology of neuropathies [ 45 , 46 , 47 , 48 ], however in our cohort we did not observed a significant correlation between these biochemical markers and neuropathy ( Supplementary Figure S9 ).…”
Section: Resultscontrasting
confidence: 73%
“…Our data showed that Bacteroidetes phylum ( Figure 6 A) specifically Parabacteroides genus ( Figure 6 B) was negatively correlated with CNFL, ( p = 0.03625 and 0.00179 respectively). Vitamins D and B have been previously reported to play a potential role in the pathophysiology of neuropathies [ 45 , 46 , 47 , 48 ], however in our cohort we did not observed a significant correlation between these biochemical markers and neuropathy ( Supplementary Figure S9 ).…”
Section: Resultscontrasting
confidence: 73%
“…Few cross-sectional studies suggest an association between 25 (OH)D level, presence and severity of peripheral neuropathies (7)(8)(9)(10)(11) and CAN (10,12) in patients with diabetes (7)(8)(9)(10)(11). Nevertheless, there are no data available about the effect of high doses of VD supplementation on CAN in people with T1DM (13,14). Molecular basis for this association is multifactorial; however, the inflammatory pathway and neurotrophin reduction might be involved in damage caused to peripheral and autonomic nerves (15,16).…”
mentioning
confidence: 99%
“…Their data show that the administration of SC144 can effectively alleviate the mechanical hyperalgesia in STZ animals compared with controls ( 33 ). A recent study has also found a significant decrease in the neuropathy severity, a decrease in the IL-6 level and an increase in the IL-10 level after treatment with cholecalciferol (40,000 IU/week) for 24 weeks in patients with T2DM and DPN ( 34 ).…”
Section: Discussionmentioning
confidence: 90%
“…Machiavelli et al have found that the serum IL-6 level increases in more than 40% of patients with DM and that the elevated IL-6 level has a significantly negative correlation with small and large nerve (33). A recent study has also found a significant decrease in the neuropathy severity, a decrease in the IL-6 level and an increase in the IL-10 level after treatment with cholecalciferol (40,000 IU/week) for 24 weeks in patients with T2DM and DPN (34). Data from the present study confirm that the vitamin D metabolite has strong associations with IL-6 (r = −0.56, P < 0.01) and TNF-α (r = −0.47, P < 0.01).…”
Section: Discussionmentioning
confidence: 93%